2018
DOI: 10.1007/978-3-030-02146-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Programming Dynamic Reconfigurable Systems

Abstract: DR-BIP is an extension of the BIP component framework intended for programming reconfigurable systems encompassing various aspects of dynamism. It relies on architectural motifs to structure the architecture of a system and to coordinate its reconfiguration at runtime. An architectural motif defines a set of interacting components that evolve according to reconfiguration rules. With DR-BIP, the dynamism can be captured as the interplay of dynamic changes in three independent directions 1) the organization of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Sources of uncertainty are multiple, including time-varying load, dynamic change due to mobility, bursty events, and most critical events such as failures and attacks. The Self-adaptation module generates objectives to cope with such situations involving imperfect knowledge and lack of predictability [2,5]. This can be achieved to some extent, using knowledge, e.g.…”
Section: Autonomic Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Sources of uncertainty are multiple, including time-varying load, dynamic change due to mobility, bursty events, and most critical events such as failures and attacks. The Self-adaptation module generates objectives to cope with such situations involving imperfect knowledge and lack of predictability [2,5]. This can be achieved to some extent, using knowledge, e.g.…”
Section: Autonomic Complexitymentioning
confidence: 99%
“…Self-organization is the ability to adapt coordination rules to changing system dynamics. We have shown that all these types of architectures can be formalized as operators taking as arguments arbitrary numbers of instances of agent and objects types [3,4,5]. We badly need theory for studying their properties in a compositional manner.…”
Section: Architecture Complexitymentioning
confidence: 99%
“…For instance, in [40,41] L2C has been extended with reconfiguration capabilities for the specific case of high performance numerical simulations. Studies have also been conducted for reconfiguration mechanisms in BIP [42].…”
Section: Reconfigurations In the Literaturementioning
confidence: 99%
“…By doing so the authors also introduce their own policy model called UseCON. -The paper "Programming dynamic reconfigurable systems" by El Ballouli, Bensalem, Bozga, and Sifakis [18] is an extension of the ISoLA 2018 and FACS 2018 papers [16,17] by the same authors. The paper focuses on programming dynamic reconfigurable systems.…”
Section: This Issuementioning
confidence: 99%